(1 + tan A + sec A)(1 + cot A - cosec A)
Answers
Answered by
0
Answer:
2
Step-by-step explanation:
(1 + tan A + sec A)(1 + cot A - cosec A)
= 1* (1 + cot A - cosec A) + tanA*(1 + cot A - cosec A)+secA(1 + cot A - cosec A)
= 1 + cot A - cosec A + tanA+tanA.cotA-tanA.cosecA + secA+secA.cotA-secA.cosecA
= 1 + cot A - cosec A + tanA+1 - (sinA/cosA)*(1/sinA) + secA+(1/cosA)(cosA/sinA) - (1/cosA)(1/sinA)
= 2 + cot A - cosec A + tanA - (1/cosA) + secA + (1/sinA) - secA.cosecA
= 2+cotA-cosecA+tanA - secA + secA + cosecA - secA.cosecA
= 2 + cotA + tanA - (1/sinA)*(1/cosA)
= 2 + (cosA/sinA) + (sinA/cosA) - (1 / sinA.cosA)
= 2 + (cos²A+sin²A)/sinA.cosA - (1 / sinA.cosA)
= 2 + (1 / sinA.cosA) - (1 / sinA.cosA)
= 2
Similar questions